2021
DOI: 10.22271/oral.2021.v7.i3d.1307
|View full text |Cite
|
Sign up to set email alerts
|

Tannerella forsythia, an orthodontic point of view

Abstract: Introduction: Tannerella forsythia, is an anaerobic, Gram-negative microorganism closely related to periodontal disease. Factors such as poor dental hygiene, fixed orthodontic appliances, etc. can cause dysbiosis in the bacterial community. Objective: To analyze the literature about the epidemiology, diagnostic methods, oral manifestations, relationship with systemic diseases and treatment of Tannerella forsythia in orthodontic patients. Methodology: Using the keywords "T. forsythia", "orthodontics", "oral man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Molecular biology tests can be used, such as the polymerase chain reaction (PCR), as well as the ELISA test. On the other hand, taking into account that periodontal disease is strictly developed by the presence and interaction of T. forsythia together with the others, clinical diagnostic methods are also taken into account, such as gingival bleeding rates, pocket depth and in periapical lesions the presence of inflammation and pain [11,16] . In a study carried out in pregnant women to study the presence and activity of periodontopathogenic bacteria, saliva samples were taken from the patients and then PCR tests were performed on each of them to quantitatively detect the amount of the 4 periodontopathogenic bacteria studied.…”
Section: Diagnosismentioning
confidence: 99%
“…Molecular biology tests can be used, such as the polymerase chain reaction (PCR), as well as the ELISA test. On the other hand, taking into account that periodontal disease is strictly developed by the presence and interaction of T. forsythia together with the others, clinical diagnostic methods are also taken into account, such as gingival bleeding rates, pocket depth and in periapical lesions the presence of inflammation and pain [11,16] . In a study carried out in pregnant women to study the presence and activity of periodontopathogenic bacteria, saliva samples were taken from the patients and then PCR tests were performed on each of them to quantitatively detect the amount of the 4 periodontopathogenic bacteria studied.…”
Section: Diagnosismentioning
confidence: 99%
“…It has been found to aid in caries development and enamel decalcification, and has been seen in areas of white-spot lesions and gingivitis post orthodontics [ 5 , 6 , 7 ] and gingivitis [ 8 , 9 ]. A systematic review found that the levels of these bacteria increased during orthodontic treatment, and three months after removal there was a significant reduction in the number of these pathogens [ 10 ]. The frequency of subgingival pathogenic bacteria was found to increase one month after the beginning of orthodontic treatment, and stayed consistently high for up to three months after the removal of orthodontic appliances [ 11 ].…”
Section: Introductionmentioning
confidence: 99%